'A Picture is Worth a Thousand Words': Multimodal Sensemaking of the Global Financial Crisis. Issue 5 (June 2018) - Höllerer, Markus A.; Jancsary, Dennis; Grafström, Maria
Through its specific rhetorical potential that is distinct from verbal text, visual material facilitates and plays a pivotal role in linking novel phenomena to established and taken-for-granted social categories and discourses within the social stock of knowledge. Employing data from the worldwide news coverage of the global financial crisis in the Financial Times between 2008 and 2012, we analyse sensemaking and sensegiving efforts in the business media. We identify a set of specific multimodal compositions that construct and shape a limited number of narratives on the global financial crisis through distinct relationships between visual and verbal text. By outlining how multimodal compositions enhance representation, theorization, resonance, and perceived validity of narratives, we contribute to the phenomenological tradition in institutional organization theory and to research on multimodal meaning construction. We argue that elaborate multimodal compositions of verbal text, images, and other visual artifacts constitute a key resource for sensemaking and, consequently, sensegiving.